2014
DOI: 10.1136/bmjopen-2013-004738
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Emergency Medicine Score (REMS) in the trauma population: a retrospective study

Abstract: ObjectiveRapid Emergency Medicine Score (REMS) is an attenuated version of the Acute Physiology and Chronic Health Evaluation (APACHE) II score and has utility in predicting mortality in non-surgical patients, but has yet to be tested among the trauma population. The objective was to evaluate REMS as a risk stratification tool for predicting in-hospital mortality in traumatically injured patients and to compare REMS accuracy in predicting mortality to existing trauma scores, including the Revised Trauma Score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
2
34

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(97 citation statements)
references
References 20 publications
3
54
2
34
Order By: Relevance
“…While REMS has been shown to be an accurate predictor of mortality in the non-surgical non-trauma medicine population [14], the score needed to be adjusted to accurately predict mortality in trauma patients. When evaluated in the trauma population, it was suggested that the GCS was underweighted and that age was over weighted [15]. As SBP is the most widely used and recorded indicator of trauma severity, mREMS was designed to include SBP instead of MAP, which was included in the original REMS score.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While REMS has been shown to be an accurate predictor of mortality in the non-surgical non-trauma medicine population [14], the score needed to be adjusted to accurately predict mortality in trauma patients. When evaluated in the trauma population, it was suggested that the GCS was underweighted and that age was over weighted [15]. As SBP is the most widely used and recorded indicator of trauma severity, mREMS was designed to include SBP instead of MAP, which was included in the original REMS score.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by our group evaluated the REMS in a trauma population and hypothesized that the weighting of GCS was too low, the weighting of age was too high, and that mechanism of injury might be able to be incorporated into the score, to better represent trauma patients [15]. For the mREMS score the relative weighting of age has been decreased and the weighting of GCS has been increased, to provide a more accurate predictor of mortality in trauma patients.…”
Section: Part I Modification Of Remsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [21], a study conducted amongst traumatically injured patients found a similar correlation between REMS and in-hospital mortality (AUC of 0.91). For our case in particular, REMS has also been proven to perform relatively well when assessing mortality risk in interhospital transfers.…”
Section: Understanding the Importance Of Rems As A Risk Assessment Tomentioning
confidence: 99%
“…Originalmente presento una buena precisión predictiva en la evaluación de pacientes no quirúrgicos 16,17 , sin embargo, los estudios más recientes mostraron su buen desempeño como predictor de mortalidad hospitalaria en victimas de trauma 41,42 y pacientes atendidos en servicios de emergencia por causas clínicas y quirúrgicas 43 Los cambios indeseables en las condiciones fisiológicas son frecuentes durante la transferencia de pacientes críticamente enfermos y pueden amenazar la vida, en especial, de pacientes dependientes de ventilación mecánica y termodinámicamente inestables. En consecuencia, en las publicaciones que analizan los factores de riesgo para eventos adversos durante o transporte destacándose el uso de ventilación mecánica y drogas vasoactivas 44 .…”
Section: Revisión De La Literaturaunclassified